Beryllium(II) Complexes of Triazene-1-Oxides - Sharma, R.; Thakur, A.K.; Rai, S.B.; Choudhary, S.N. (Asian Journal of Chemistry, 2010)
Beryllium (II) complexes of triazene-1-oxides were synthesised and characterised using elemental analyses, conductance, molecular complexities in freezing benzene and IR spectral studies. The complexes obtained were invariable four coordinate and the stereochemistry tetrahedral due to its ionic size and availability of bonding orbitals. Several recrystallisations from acetone gave consistent characterisation data proving that the beryllium complexes obtained were definite molecular addition compounds rather than loose adducts.